The identity of Tokays (Squamata: Gekkonidae: Gekko) from Hong Kong - Ho, Siu-Kit; Chan, Hon-Ki; Karraker, Nancy E. (Zootaxa, 2023)
The Tokay gecko (Gekko gecko), found throughout Southeast Asia and India, is a heavily harvested species of high commercial value. Recent studies have supported the elevation of the black morph of Tokay gecko, found only in southern China and northern Vietnam, to the species Gekko reevesii. Previous genetic studies focused on specimens of G. reevesii from southwestern populations. Hong Kong, in southeastern China, has native populations of G. reevesii. To verify the identity of G. reevesii in Hong Kong, we employed three mitochondrial genes (COI, Cytb & ND2) and constructed a matrilineal genealogy using other specimens from Guangxi (southwestern China) and northern Vietnam, as well as G. gecko from a wide range of Southeast Asian countries. Our study confirmed that G. reevesii occurs naturally in Hong Kong, but one exotic population of G. gecko, likely a translocation from international trade, was also revealed. Our study did not reject the species ranking of G. reevesii. Moreover, like previous studies, we recovered a paraphyletic G. gecko, which may reflect a species complex, hybridization or incomplete lineage sorting. More extensive sampling of the two species over a broader range of their asserted distribution together with the use of both mitochondrial and nuclear DNA are required to better investigate their biogeography.